Antimicrobial activity of stachytarpheta jamaicensis against fish pathogenic bacteria and its toxicity on brine shrimp - Muhammad Haziq Ismail (2022)
Stachytarpheta jamaicensis has been used traditionally in humans to treat digestive problems, allergies, respiratory conditions, hepatitis, wounds and ulcers in various countries. This valuable plant is known to have some pharmacological effects like antimicrobials due to its active phytochemicals. The objectives of this study were (i) to determine the antimicrobial activity of S. jamaicensis ethanolic extract against Vibrio parahaemolyticus, Streptococcus agalactiae and Aeromonas hydrophila and (ii) to investigate its toxicity effect on brine shrimp. S. jamaicensis was collected at Tanah Merah, Kelantan and the ethanolic extract of the plant was prepared by using the whole plant including the stems and leaves. Disc diffusion assay was done to assess the antibacterial properties of S. jamaicensis ethanolic extract. Then, brine shrimp lethality assay was employed to determine the possible toxicity of ethanolic extract of S. jamaicensis. LC50 was calculated by using Probit analysis. Results revealed that the ethanolic extract of S. jamaicensis has the most effective antimicrobial properties towards A. hydrophila but less effect on V. parahaemolyticus and S. agalactiae. The extract is also safe to use as the LC50 calculated was 26915.35 μg/ml which is considered non-toxic based on Meyer’s toxicity index. Current study showed ethanolic extract of S. jamaicensis possessed antibacterial properties against A. hydrophila and safe to be used as therapeutic application in aquaculture. Keywords: Antimicrobial, Brine shrimp, Disc diffusion assay, Ethanolic extract, Stachytarpheta jamaicensis, Toxicity